Halosulfuron Absorption, Translocation, and Metabolism in White and Adzuki Bean. Issue 4 (December 2016) - Li, Zhenyi; Kessler, Kallie C.; Alves de Figueiredo, Marcelo Rodrigues; Nissen, Scott J.; Gaines, Todd A.; Westra, Philip; Van Acker, Rene C.; Hall, Christopher; Robinson, Darren E.; Soltani, Nader; Sikkema, Peter H.
Abstract : Halosulfuron-methyl, a sulfonylurea herbicide, was registered for broadleaf weed control in dry bean. This herbicide has an adequate margin of crop safety in white bean, but causes unacceptable injury to adzuki bean. Halosulfuron-methyl absorption, translocation, and metabolism were evaluated in white and adzuki bean using radiolabeled herbicide to determine if differences in these parameters could explain the difference in crop safety between these two species. Adzuki bean had more rapid halosulfuron-methyl absorption than white bean. Adzuki bean reached 90% absorption ( t 90 ) 26.2 h after treatment (HAT), whereas white bean required 40.1 HAT to reach t 90 . The maximum halosulfuron-methyl absorption was higher in adzuki bean (75.7%) than in white bean (65.3%). More 14 C-halosulfuron was translocated to the apex, first trifoliate, stem above the treated leaf, and roots in aduzki bean than in white bean. The maximum radioactivity translocated out of treated leaf was higher in adzuki bean (17.7%) than in white bean (12.1%). Halosulfuron-methyl was broken down to the same metabolites in white and adzuki bean. The half-life of halosulfuron-methyl in adzuki bean was 16 HAT, compared with less than 6 HAT in white bean. More herbicide remained as the free acid in adzuki bean compared with white bean over the entire 48-h time course. The differential tolerance of white and adzuki bean to halosulfuron can be attributed to greater absorption and translocation and decreased metabolism in adzuki bean.